Review on Carburizing Case Quality of Carburizing and Hardening Gear - Ma Wei; Lu Jun (Jixie chuandong)
The carburizing technology is widely used in gear heat treatment to improve the comprehensive performance of gear surface wear resistance,contact figure strength and bending fatigue strength,etc. The carburizing case quality must be strictly controlled to obtain the best comprehensive performance of gear. The evaluation requirements of the indexes of effective hardening depth,carbide and residual austenite in the carburizing case are introduced. Meanwhile,combining with the current situation of quality controlling specification and relevant standards of the carburizing layer at home and abroad,some suggestions are put forward for the carburizing case quality evaluation specification.